Correlation Between Mobility and COVID-19 Cases in Surabaya City, Indonesia - Alawy, Gholiqul Amrodh; Wicaksono, Achmad; Suharyanto, Agus (Civil and Environmental Science Journal (CIVENSE), 2021)
The number of COVID-19 cases in Surabaya was one of the highest in Indonesia at the beginning of the pandemic. This study aims to determine the mobility and activity patterns of the people of Surabaya during the COVID-19 pandemic and find a correlation between people mobility and the number of COVID-19 cases in Surabaya City using Pearson’s Coefficient of Correlation (PCC). The data used are mobility data at Gubeng Station, Purabaya Terminal, Waru Utama toll gate, and COVID-19 Community Mobility Reports. The mobility pattern of the people of Surabaya City in 2020 is divided into 5 phases, namely the normal condition phase (F0), the pandemic’s initial phase (F1), the PSBB phase (F2), the transition of AKB phase (F3), and the AKB phase (F4). This study indicates that the number of people in transit stations and residential areas has a high correlation with the number of COVID-19 cases. In addition, the type of mobility that has the most effect on increasing the number of COVID-19 cases is the mobility of bus transportation.